Aplikasi Penerimaan Siswa Baru dan Informasi Akademik Berbasis Web - Jufrison Benyamin Merukh; Emerensiana Ngaga; Frengky Tedy (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
New Student Admission is an activity that will always be carried out every year by schools, both public and private schools in attracting new students. The process of admitting new students needs doing quickly and precisely to support the educational process in each school. There are currently not many schools in East Nusa Tenggara that develop new student admission information system and Academic Information online. With the benefit and ease of existing technology, this new student admission information system and Academic Information set by each school. The New Student admission and Academic Information System at the Christian High School Kesetnana Soe currently still use a manual system where information on new student admissions distributed through brochures, the registration process for new students is still by filling in the form provided by the committee, data entry is not accurate, and it takes too long. Of these problems, the purpose of this research is to build an application to assist the school in the web-based admission process for the process to run effectively and efficiently. This software development uses the waterfall method, and the programming language used is PHP and MYSQL as the database. The result of this research is a system that can help make it easier for students to register and see the results of graduation anywhere and make it easier for teachers to input school academic information data online.